La motivation à apprendre des étudiants de français et de littérature au cégep - Louise Ménard; Diane Leduc (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
A number of studies confirm that in general and vocational college, the successful completion of the first French Literature course is an indicator of student retention and graduation. Although teachers of this discipline often blame student motivation for the high level of failure and withdrawal for this course, no research has looked at the issue from a motivational standpoint. It is in this context that the research first tries to determine if there is indeed a motivation issue among students starting their first French Literature course and then measures the evolution of the level of motivation among students registered in this course. To do this, the level of motivation of 1105 students belonging to 48 course groups was measured at the beginning and end of the semester according to the motivation measurement scale developed by Pintrich (1988, 1989). Analysis of the questionnaire results reveals that the students’ overall motivation level is rather high at the beginning of the semester and decreases at the end of the semester. Moreover, the motivation level of seven course groups stayed unchanged or increased between the beginning and the end of the semester. An interview conducted with 11 students from these course groups helps to describe the teaching practices that seem to play a role in the maintenance or increase of the motivation level.